Handbook of African economic development - Carmody, Pádraig Risteard; Murphy, James T. (Associate professor of geography) (Elgar handbooks in development, 2024)
"The Handbook of African Economic Development explores the diverse nature of economic advancement in Africa, spanning from pre-colonial times to the present day. Expansive in scope, it offers both orthodox and heterodox perspectives on the subject, and what it means for the continent. Going beyond traditional metanarratives, this dynamic Handbook provides a historically grounded, data-informed analysis of African economic development, taking into account external pressures and internal structural inequalities. Contributors map out the key debates surrounding the topic before assessing historical contexts, the effect of global networks, current industries and institutions, and both rural and urban developments. The Handbook contends with the future of economic development in Africa, particularly in the context of climate change, continuing decolonisation and Africapitalism. With a global team of authors providing a range of perspectives, this unique Handbook will prove crucial reading for students and scholars of African studies, development studies, geography and economics. It will also prove to be a fascinating read for anyone interested in non-conventional, postcolonial approaches to these disciplines"--